Community‐based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability - Aniko Sabo; David Murdock; Shannon Dugan; Qingchang Meng; Marie‐Claude Gingras; Jianhong Hu; Donna Muzny; Richard Gibbs (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. Methods Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. Results All five families enrolled in the study opted‐in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow‐up in an appointment with a board certified clinical geneticist. Conclusion Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing‐based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.